2010
DOI: 10.2353/ajpath.2010.090322
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of L-Selectin in Contact Hypersensitivity Responses Augmented by Auditory Stress

Abstract: Stress affects the pathophysiology of cutaneous immune reactions, including contact hypersensitivity (CH) in individuals sensitized with sensitizing hapten, where local endothelial cell activation plays a critical role. To clarify the effects of stress in cutaneous immune reactions, we selected a CH model using annoying sound as a stress. Furthermore, we conducted the stress experiments by using selectin-deficient mice to determine the involvement of selectin molecules regarding local endothelial activation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…In these experiments, SP activation of DC during the effector phase of a Th1-driven inflammation triggered a massive and rapid LC mobilization out of the epidermis and enhanced inflammation. An inflammation-promoting effect of SP signaling was also demonstrated in other Th1 and neurogenic inflammation-dominated neuroimmune constellations, such as during the elicitation of contact hypersensitivity (7,58,59), during provocation of AlD (32)(33)(34), in hair loss (60), and in healthy murine skin and lymphocytes (34,39,40). This effect appears to be further facilitated by stress-and nerve growth factor-induced plasticity of the peripheral nervous system and malfunctioning HPA responsiveness (32,34,39,61,62).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In these experiments, SP activation of DC during the effector phase of a Th1-driven inflammation triggered a massive and rapid LC mobilization out of the epidermis and enhanced inflammation. An inflammation-promoting effect of SP signaling was also demonstrated in other Th1 and neurogenic inflammation-dominated neuroimmune constellations, such as during the elicitation of contact hypersensitivity (7,58,59), during provocation of AlD (32)(33)(34), in hair loss (60), and in healthy murine skin and lymphocytes (34,39,40). This effect appears to be further facilitated by stress-and nerve growth factor-induced plasticity of the peripheral nervous system and malfunctioning HPA responsiveness (32,34,39,61,62).…”
Section: Discussionmentioning
confidence: 96%
“…In allergic disorders-especially in people with an atopic predisposition-the net effect of the stress response was generally reported to contribute to acute exacerbation and even onset of disease (2)(3)(4)(5)(6)(7). The key mechanisms involved are altered immune competence and neuronal plasticity after stress experience as a result of an HPA-and SA-generated Th2 bias on the one hand and local proinflammatory NNA activation on the other hand (8)(9)(10).…”
mentioning
confidence: 99%
“…While a review of these studies is beyond the scope of this manuscript, taken together, they suggest that changes in leukocyte adhesion molecule conformation/expression may mediate aspects of both the mobilization and trafficking effects of stress and stress hormones. In support of a role for CD62L in mediating the immuno-enhancing effects of short-term stress, a recent study has shown that the acute stress-induced enhancement of skin cell-mediated immunity is significantly decreased in CD62L deficient mice (Bae et al, 2011). Other studies have suggested that glucocorticoid hormones suppress neutrophil CD62L mRNA expression and that this induces a decrease in cell-surface protein expression of CD62L that is correlated with a glucocorticoid-induced neutrophilia (Weber et al, 2001).…”
Section: Discussionmentioning
confidence: 99%